Monetary Policy Responsive to Global Geopolitics: An Analysis of Its Impact on Indonesia's Growth and Stability - Rosidah, Rosidah (Journal of Management Economic and Financial, 2025)
Global geopolitical uncertainty, including trade wars, regional conflicts, and tensions between major countries, have increased risks to the macroeconomic stability of developing countries, including Indonesia. These external dynamics have an impact on inflation, exchange rates, capital flows, and national economic growth. Therefore, responsive monetary policy is needed to maintain price stability while supporting sustainable economic growth. This study aims to analyze the influence of global geopolitical shocks on Indonesia's economic stability, evaluate the effectiveness of monetary policy in the face of external uncertainties, and formulate a responsive and adaptive monetary policy strategy. The research method uses a mixed-method approach. Quantitative analysis was conducted using the Vector Autoregression (VAR) and Vector Error Correction Model (VECM) models to assess the dynamic relationship between global geopolitical indicators, inflation, exchange rates, and economic growth. Meanwhile, a qualitative approach is carried out through a systematic literature review of the experiences of developing countries in facing global pressures. Secondary data was obtained from Bank Indonesia, BPS, IMF, and World Bank for the period 2010–2024. The results of the study show that global geopolitical shocks increase inflation, encourage rupiah depreciation, and increase capital outflow risks. Responsive monetary policy, especially through BI Rate instruments and market interventions, has proven to be able to cushion medium-term pressures. However, the effectiveness of monetary policy is highly dependent on coordination with fiscal and macroprudential policies. These findings underscore the importance of including global geopolitical variables in Indonesia's monetary policy formulation to ensure inclusive growth and long-term stability.